Feminist research and action methodology : the experiences of the Caribbean Association for Feminist Research and Action. - DEARE, Fredericka M. (1995)
Examines some of the issues faced by women in the two areas of Caribbean societies, viz; the agricultural sectorand the legal system. Traces the development of the contemporary women's movement and CAFRA's evolution out of the needs of the movement. Describes and analyses the methodological aspects of the Women in Caribbean agriculture project and the women and the law project, their differences and constraints on how they were dealt with.